PENGARUH PENGGUNAAN KARTU KONTROL KONSUMSI TABLET TAMBAH DARAH TERHADAP PENINGKATAN KADAR HB PADA REMAJA PUTRI DI MTS MIFTAHUL AULA BANGKAL - Normala Sari; Yuniarti; Nur Rohmah Prihatanti; Erni Yuliastuti (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Anemia among adolescent girls remains a significant public health problem that affects health status and future reproductive readiness. One of the efforts to prevent anemia is through the consumption of iron supplement tablets. However, adherence to iron tablet consumption among adolescent girls is still low. Therefore, a monitoring tool such as a control card is needed to improve adherence and support the increase of hemoglobin (Hb) levels. This study purpose to determine the effect of using a control card for iron supplement tablet consumption on the increase of hemoglobin levels among adolescent girls at MTs Miftahul Aula Bangkal in 2025. Method: This study employed a one-group pretest–posttest design. The sample consisted of 30 adolescent girls selected using purposive sampling. Hemoglobin levels were measured before and after the implementation of the iron tablet consumption control card. Data were analyzed using the Paired Sample T-Test. Results: The results showed an increase in hemoglobin levels after the use of the control card for iron supplement tablet consumption. The Paired Sample T-Test revealed a t value of 7.026 with a significance level (p) of 0.005 (p < 0.05), indicating a statistically significant difference in hemoglobin levels before and after the intervention. Conclusion: The use of an iron tablet consumption control card has a positive and significant effect on increasing hemoglobin levels among adolescent girls. The control card is recommended as a monitoring tool to improve adherence to iron tablet consumption in anemia prevention efforts.